Nutritional status of pregnant women and its impact on fetal development: A qualitative study - Rika Riyandani; Lilis; Eka Fitri Amir (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Maternal nutrition plays a fundamental role in ensuring optimal fetal growth and development. Inadequate nutrient intake during pregnancy increases the risk of complications such as low birth weight, preterm birth, and developmental delays. This study examines the nutritional status of pregnant women and its impact on fetal development, with a focus on dietary practices and maternal perceptions of nutrition. Methods: This qualitative study involved in-depth interviews with 20 pregnant women selected through purposive sampling. Data were collected using semi-structured interview guides and analyzed through thematic content analysis. The study focused on participants’ nutritional knowledge, dietary behaviors, access to nutritious foods, and perceptions of fetal development. Results: Findings revealed three major themes: (1) Maternal nutritional awareness, where most participants had basic knowledge of essential nutrients but lacked detailed understanding of recommended dietary intake; (2) Dietary practices and influencing factors, showing that meal patterns were often inconsistent due to socioeconomic constraints, food aversions, and cultural beliefs; and (3) Perceived impact on fetal development, with participants acknowledging the importance of nutrition but demonstrating limited ability to maintain balanced diets. Poor nutritional status was commonly associated with symptoms such as fatigue, inadequate weight gain, and concerns about fetal growth. Conclusion: The study concludes that suboptimal nutritional status among pregnant women may have a negative impact on fetal development. Improving maternal nutrition requires targeted educational interventions, enhanced access to nutritious foods, and culturally appropriate health counseling. Collaboration between healthcare providers, families, and community programs is essential to promote healthier dietary behaviors during pregnancy. Further research is recommended to explore effective strategies for improving maternal dietary adherence.